Problem-based Learning as Methodological Technique to Develop Critical Thinking - María Magdalena Barahona Lino, Concepción Elizabeth Marcillo García (International Journal of Advanced Science and Technology, 2020)
An investigation related to the weak development of critical thinking is carried out in second year high school students of the Educational Unit "Quince de Octubre" in the canton of Jipijapa, so the objective was to analyze the contribution of problem-based learning such as methodological technique in the development of the critical capacity of Biology students. In the development of the research, 55 students from the Biology course were selected, who participated through the application of practical exercises using the Problem-Based Learning technique, which was worked methodologically following the learning cycle of experience, reflection, conceptualization and application (ERCA). To confront the results, a diagnosis was carried out where the level of development of critical thinking of the students was determined, to observe the achievements after the intervention, verifying that the technique helped students in the development of their critical thinking. The research is descriptive - explanatory, qualitative and quantitative methods were used for the analysis, making use of research techniques and instruments such as observation, test, survey questionnaire. As a result of the investigation, it was obtained that the students improved their capacity for analysis and criticality.